Electrode migration after cochlear implantation. (4th March 2021) - von Mitzlaff, Christian; Dalbert, Adrian; Winklhofer, Sebastian; Veraguth, Dorothe; Huber, Alexander; Röösli, Christof
Abstract : Objective: To investigate impedance change of cochlear implant (CI) electrodes from Cochlear TM in patients with straight and precurved electrodes, and to determine if impedance change of the basal electrodes are indicative for cochlear electrode migration. Methods: Retrospective case series at an academic tertiary referral center. Five hundred sixty patients (414 precurved, 146 straight) received a CI from Cochlear TM between January 2010 and August 2018. Electrode impedance measured intraoperatively and during follow-up has been assessed. In case of impedance change of the 3 most basal electrodes a computer tomography (CT) scan has been performed. Cochlear position of the electrode array has been determined and compared to the one day postoperative electrode position (plain radiography). Results: Changes in electrode impedance in the basal electrodes occurred in 2.1% ears ( n = 12). CT scan was available in 9 patients and revealed a migration of the electrode array in 6 patients. Straight electrode types showed a significantly higher migration rate than precurved electrode types (4.1% vs 0%). Conclusions: Electrode impedance is a useful tool to investigate electrode array integrity as well as to raise suspicion of possible electrode migration. Patients implanted with a straight electrode from Cochlear TM array might benefit from lead wire fixation.